2018
DOI: 10.1080/13880209.2018.1446031
|View full text |Cite
|
Sign up to set email alerts
|

Vascular mechanisms underlying the hypotensive effect of Rumex acetosa

Abstract: Context:Rumex acetosa L. (Polygonaceae) is well known in traditional medicine for its therapeutic efficacy as an antihypertensive.Objective: The study investigates antihypertensive potential of crude methanol extract (Ra.Cr) and fractions of Rumex acetosa in normotensive and hypertensive rat models and probes the underlying vascular mechanisms.Materials and methods: Ra.Cr and its fractions were tested in vivo on normotensive and hypertensive Sprague-Dawley rats under anaesthesia for blood pressure lowering eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Further, ERA exhibits endothelium-independent modulation of calcium entry through voltage-gated Ca +2 channels and release from internal calcium stores. These actions likely underlie its antihypertensive influence in normotensive and salt-induced hypertensive rats ( Qamar et al, 2018 ). Ahmad et al (2016) reported that an essential oil isolated from R. hastatus inhibits cholinesterase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Further, ERA exhibits endothelium-independent modulation of calcium entry through voltage-gated Ca +2 channels and release from internal calcium stores. These actions likely underlie its antihypertensive influence in normotensive and salt-induced hypertensive rats ( Qamar et al, 2018 ). Ahmad et al (2016) reported that an essential oil isolated from R. hastatus inhibits cholinesterase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas it was established that calcium influx via VDCCs and ROCs amplified the calcium contents of cytosol in response to high K + and P.E addition to organ bath [52,53], which resultantly trigger a persistent contractions. It has also been demonstrated that calcium channel blockers possesses antioxidant properties which reduce endothelial dysfunction by restoring NO availability [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it was established that calcium influx via VDCCs and ROCs amplified the calcium contents of cytosol in response to high K + and P.E addition to organ bath [ 52 , 53 ], which resultantly trigger a persistent contractions. It has also been demonstrated that calcium channel blockers possesses antioxidant properties which reduce endothelial dysfunction by restoring NO availability [ 54 , 55 ]. It has also been demonstrated that nifedipine, a standard CCBs, preserves endothelial integrity in patients with hypertension [ 56 ] and hence E. hirta , F. indica and C. decidua showed additional antihypertensive mechanism in arsenic-induced hypertensive rats via improving the endothelium damage by additional CCBs type constituents.…”
Section: Discussionmentioning
confidence: 99%
“…"This herb is used in food products with medicinal properties related to its tannin content [15]. Previous studies reported that Rumex acetosa possessed antioxidant, anti-hypertensive, antiviral, and anticancer effects" [16,17,18].…”
Section: Introductionmentioning
confidence: 99%